Effect of lubrication on the wear behaviour of CrN coating deposited by PVD process. (2019) - Singh, Shailesh Kumar; Chattopadhyaya, Somnath; Pramanik, A.; Kumar, Sanjeev; Basak, A.K.
This paper investigates the effect of SAE grade 20W50 engine oil as a lubricant on the wear behaviour of chromium nitride (CrN) coating deposited by PVD process at higher loads and speeds by pin on disc tribometer. The specific wear rate ranges from 9.82 × 10 -5 to 2.87 × 10 -5 mm 3 /Nm in dry condition whereas in lubricated condition 0.97 × 10 -5 to 0.19 × 10 -5 mm 3 /Nm. Successive increase of speed and load rises the temperature of wear track from 65°C to 178°C in dry condition while 34°C to 40°C in lubricated conditions results to decrease in friction coefficient, which has immense influence on the wear resistance of coating. The wear mechanism of the coatings was analysed by SEM and EDS and found deformation, cracks and, nitride particle pull-out, built up edge formation, erosion and adhesive wear coupled with oxidation wear. The highlights of the paper are: 1) tribology of CrN coating against cylinder liner material as counter face summarised; 2) research has practical applications for piston ring with the influence of engine oil; 3) temperature ranges from 65°C to 178°C in dry and 34°C to 39°C in lubrication during wear test; 4) the wear mechanism is combination of three body abrasion, metal transfer and oxidation.